ANALYSIS OF INVESTMENT DECISIONS, FUNDING DECISIONS, FINANCIAL RISK MANAGEMENT IMPACTS ON FINANCIAL DISTRESS WITH MODERATION OF GOOD CORPORATE GOVERNANCE IN MANUFACTURING INDUSTRY SECTORS LISTED ON THE INDONESIA STOCK EXCHANGE - pristiana, ulfi; istiono, istiono (Ekspektra : Jurnal Bisnis dan Manajemen, 2020)
Globally, the development of the manufacturing industry can be used as a parameter for national industrial development in a country. Therefore, to keep manufacturing companies continuing or developing, it is necessary to have clear policies in developing this manufacturing industry. Some manufacturing companies did not develop as expected because they experienced Financial Distress (FD). The study population was conducted at several manufacturing companies that experienced financial distress with the study period from 2015-2018. The research sample was determined by non-random sampling (purposive sampling) to determine which companies are included in the Financial Distress category. Of the 163 manufacturing companies listed on the Indonesia Stock Exchange / IDX for the 2015-2018 period, 32 companies were included in the FD category. In this study, Smart PLS software is used to analyze and prove the effect of investment decisions, capital decisions, and financial risk management on financial distress by using good corporate governance / GCG as a moderating variable. The results showed that capital decisions, financial risk management, and good corporate governance had a significant effect on financial distress, except that investment decisions had no significant effect on financial distress. GCG significantly moderates the effects of investment decisions, capital decisions, and financial risk management on financial distress.